Five-phase induction motor drive for electric vehicle with high gain switched-inductor quasi impedance source inverter - Yaramasu Suri Babu; Koritala Chandra Sekhar (Institute of Advanced Engineering and Science, 2022)
Switched-inductor quasi-impedance source inverter (SL-qZSI) with high gain fed five-phase induction motor drive for electric vehicle (EV) applications is proposed in this paper. Multi-phase electric machines have been predicted for application where the entire system should have better reliability and demanded power per phase is low especially for autonomous applications like EVs. To supply variable voltage and frequency to multi-phase machines, multi-phase inverters are required. SL-qZSI offers enhanced boost capability with respect to traditional impedance source converters by inserting three diodes and only one inductor to the basic quasi-impedance source inverter (qZSI). Also, SL-qZSI offers withstanding capability during voltage dip results line harmonics are diminished; enhances reliability of inverter; and extended output voltage range. The key idea of this paper is to design and develop a high performance and highly reliable SL-qZSI fed five-phase Induction Motor drive and validate the proposed system depends on results of Simulation with the help of MATLAB; these findings were comparable to the similar type of existing converters. We can notice from the performance analysis of the proposed system that it can provide enhanced voltage boosting capability and proved that it has significant potential for the suggested multi-phase variable speed drive (VSD) system.